The Influence of Shared Consumption on Product Efficacy Perceptions: The Detrimental Effect of Sharing with Strangers - Lteif, Lama; Block, Lauren; Kramer, Thomas; Hada, Mahima (Journal of Marketing Research, 2024)
Opportunities for the shared consumption of publicly available products that once might have been considered personal-use only, such as hand sanitizers and shampoos, are proliferating in the consumer environment. This work explores shared product consumption in these underresearched, but now ubiquitous, contexts. The authors suggest and find, over a series of five studies and across a variety of product domains, that sharing a product with strangers (i.e., sharing-out) engenders a lower sense of identification with the product, which leads to lower perceived product efficacy. They further show that the dampening effect of sharing-out on efficacy perceptions is limited to consumers high in self–brand connection.